2000
DOI: 10.1111/1469-7610.00644
|View full text |Cite
|
Sign up to set email alerts
|

The Familial Aggregation of the Lesser Variant in Biological and Nonbiological Relatives of PDD Probands: a Family History Study

Abstract: These findings on the familial aggregation of the lesser variant suggest that the genes for PDD also confer susceptibility to the lesser variant and that PDD may be a genetically heterogeneous disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
97
2
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 28 publications
4
97
2
4
Order By: Relevance
“…These findings are consistent with our hypothesis that these problems may be co-morbidities and not clinical features of ASD, at least not in all cases. We acknowledge that these relations pertain to recognized or diagnosed mental health problems and that more detailed assessment would likely have identified a larger number of affected relatives (e.g., Szatmari et al 2000). As a result, we may have underestimated the magnitude of the relationship between family history and child psychiatric symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with our hypothesis that these problems may be co-morbidities and not clinical features of ASD, at least not in all cases. We acknowledge that these relations pertain to recognized or diagnosed mental health problems and that more detailed assessment would likely have identified a larger number of affected relatives (e.g., Szatmari et al 2000). As a result, we may have underestimated the magnitude of the relationship between family history and child psychiatric symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…More recent data from Goin-Kochel et al (2007), suggest no increase risk of autism by sex of proband. If the risk of the broader autism phenotype in relatives instead is used as the outcome measure, there is still no difference by sex of proband (Pickles et al 2000;Szatmari et al 2000). Another possibility is that the genetic factors affecting risk are different than those affecting severity in general, or cognitive impairment in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also focused on familial aggregation and the presence of common underlying liability genes, thus investigating possible associations between child characteristics (e.g., the severity of autism symptoms, cognitive ability, level of functioning) as well as parent characteristics (e.g., cognitive and linguistic abilities) and the manifestations of BAP-related difficulties among unaffected relatives of individuals with autism (Bishop et al 2004a;Dawson et al 2007;Murphy et al 2000;Pickles et al 2000;Starr et al 2001;Szatmari et al 2000). For example, Szatmari et al (2000) reported more BAP manifestations in relatives of children with highfunctioning autism compared to children with low-functioning autism as well as more BAP manifestations in multiplex families (i.e., families with two affected children with autism) compared to simplex families (i.e., families with one child with autism).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Szatmari et al (2000) reported more BAP manifestations in relatives of children with highfunctioning autism compared to children with low-functioning autism as well as more BAP manifestations in multiplex families (i.e., families with two affected children with autism) compared to simplex families (i.e., families with one child with autism). Pickles et al (2000) revealed a significant association between relatives' BAP manifestations and symptom severity in the children with autism, but only for children with speech, not for children without speech.…”
Section: Introductionmentioning
confidence: 99%